2011
DOI: 10.1523/jneurosci.2785-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Lateralized Theta Wave Connectivity and Language Performance in 2- to 5-Year-Old Children

Abstract: Recent neuroimaging studies support the view that a left-lateralized brain network is crucial for language development in children. However, no previous studies have demonstrated a clear link between lateralized brain functional network and language performance in preschool children. Magnetoencephalography (MEG) is a noninvasive brain imaging technique and is a practical neuroimaging method for use in young children. MEG produces a reference-free signal, and is therefore an ideal tool to compute coherence betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
66
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 31 publications
1
66
0
6
Order By: Relevance
“…Previously, it has been demonstrated that lateralization of MEG sensor coherence in the theta band was associated with language performance in young children (Kikuchi et al, 2011). Moreover, preservation of this sensor-level coherence was found to be related to language abilities in young children with autism spectrum disorder, suggesting that development of typical network connectivity dynamics is linked with preservation of language abilities in clinical child populations (Yoshimura et al, 2013).…”
Section: Discussionmentioning
confidence: 96%
“…Previously, it has been demonstrated that lateralization of MEG sensor coherence in the theta band was associated with language performance in young children (Kikuchi et al, 2011). Moreover, preservation of this sensor-level coherence was found to be related to language abilities in young children with autism spectrum disorder, suggesting that development of typical network connectivity dynamics is linked with preservation of language abilities in clinical child populations (Yoshimura et al, 2013).…”
Section: Discussionmentioning
confidence: 96%
“…functional MRI and PET), noninvasive, low stress functional brain measurement methods, such as MEG and NIRS, have recently been proven feasible for use in preschool-age children, and reports have begun to appear regarding various cognitive processes in this age group [1,2,[9][10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Functional neuroimaging techniques such as magnetoencephalography (MEG) and near-infrared spectroscopy (NIRS) have advantages for use in young children because they are noninvasive, less stressful, and less restrictive than other methods [1,2]. However, when used alone, there are technical drawbacks intrinsic to MEG and NIRS in that these methods measure cortical activities without anatomical information of the brain.…”
Section: Introductionmentioning
confidence: 99%
“…For example, fMRI (functional magnetic resonance imaging) studies have shown that the functional connectivity between some brain regions estimated by BOLD signals during resting-state could predict, or at least correlate with, individual differences of cognitive abilities (e.g., [1,2]). Other neuroimaging methods (e.g., magnetoencephalography; MEG) can also measure the resting-state brain activity and associate the activity with cognitive abilities or disorders [3,4]. For example, Tsiaras et al [3] reported that the non-linear characteristics of resting-state functional connectivity estimated from MEG signals might be available as a biomarker for autism spectrum disorder for adult subjects.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Tsiaras et al [3] reported that the non-linear characteristics of resting-state functional connectivity estimated from MEG signals might be available as a biomarker for autism spectrum disorder for adult subjects. Kikuchi et al [4] conducted a resting-state study for children and found that the lateralization of theta band oscillation correlated with the language ability in the early development period.…”
Section: Introductionmentioning
confidence: 99%